SPE Europec Featured at 81st EAGE Conference and Exhibition 2019
DOI: 10.2118/195510-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmentally Friendly Drilling Fluid Additives in Water-Based Drilling Mud

Abstract: Drilling wastes generated in large volumes is recognized to have many effects on the environment. Several techniques have been applied by the oil and gas industry to overcome the impacts of drilling waste on the environment, an example of these techniques is using environmentally friendly drilling fluid additives. This work investigates the potential of using Fibrous Food Waste Material (FFWM) as an environmentally friendly drilling fluid additive. This material was prepared in-house. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In this paper, mandarin peel powder was used to determine its influence on rheological and filtration properties of bentonite-based drilling fluid. This type of food waste was chosen since mandarin is in second place in terms of fruit production in Croatia [29], and since other authors have found some useful properties of mandarin peel powder as an additive in drilling fluid [28,36,37].…”
Section: Weighting Agentsmentioning
confidence: 99%
“…In this paper, mandarin peel powder was used to determine its influence on rheological and filtration properties of bentonite-based drilling fluid. This type of food waste was chosen since mandarin is in second place in terms of fruit production in Croatia [29], and since other authors have found some useful properties of mandarin peel powder as an additive in drilling fluid [28,36,37].…”
Section: Weighting Agentsmentioning
confidence: 99%
“…Therefore, CMC from empty oil palm fruit bunches met the standards of Industrial CMC. Al-Hameedi et al (2019) reported the use of 5 gr of CMC from Carton plus 4.5 gr of Na2CO3 increased the thickness of mud cake by almost over 0.3cm, from 0.19 and 0.214 cm to 0.54cm, at a concentration of 1% (10 gr) and 2% (20 gr) of CMC.…”
Section: Mud Cakementioning
confidence: 99%
“…In 2018, Assi, used potato starch as drilling fluid additive and results showed improved filtration loss and mud cake consistency also, it increased basic rheological parameters in high pH media [8]. In 2019, Al-Hameedi et al worked on introducing grass powder (GP) as drilling fluid additive and results showed viscosity improvement from 8 to 9 cP, gel strength improvement from 22 to 26 lb/100ft 2 and 28% reduction in fluid loss [9]. In 2021, Novriansyah reported that 2 wt% of cassava starch is able to improve drilling fluid filtration properties through reducing fluid loss from 5.2 to 1.6 ml as well as improving the gel strength from 0.4 to 0.6 lb/100ft 2 [10].…”
Section: -Introductionmentioning
confidence: 99%
“…Results showed better filtration properties and rheological properties with TiO2 and PP [11]. ZnO nanoparticles are widely recognized as safe, biocompatible and technological material that has caught profound attention due to its distinguished performance as photoluminescence agents in biosensors, antibacterial agents in many products, and UV-absorbers in coating materials [7][8][9][10][11][12]. ZnO nanoparticles are known to have stable physical and chemical properties during applications as they show the least sensitivity to temperature and pressure variation, indicating a stable elemental compound and favored to be used for industrial applications [13].…”
Section: -Introductionmentioning
confidence: 99%